Demonstration of electron diffraction from membrane protein crystals grown in a lipidic mesophase after lamella preparation by focused ion beam milling at cryogenic temperatures - Polovinkin, Vitaly; Khakurel, Krishna; Babiak, Michal; Angelov, Borislav; Schneider, Bohdan; Dohnalek, Jan; Andreasson, Jakob; Hajdu, Janos (Journal of applied crystallography, 2020)
Electron crystallography of sub-micrometre-sized 3D protein crystals has emerged recently as a valuable field of structural biology. In meso crystallization methods, utilizing lipidic mesophases, particularly lipidic cubic phases (LCPs), can produce high-quality 3D crystals of membrane proteins (MPs). A major step towards realizing 3D electron crystallography of MP crystals, grown in meso, is to demonstrate electron diffraction from such crystals. The first task is to remove the viscous and sticky lipidic matrix that surrounds the crystals without damaging the crystals. Additionally, the crystals have to be thin enough to let electrons traverse them without significant multiple scattering. In the present work, the concept that focused ion beam milling at cryogenic temperatures (cryo-FIB milling) can be used to remove excess host lipidic mesophase matrix is experimentally verified, and then the crystals are thinned to a thickness suitable for electron diffraction. In this study, bacteriorhodopsin (BR) crystals grown in a lipidic cubic mesophase of monoolein were used as a model system. LCP from a part of a hexagon-shaped plate-like BR crystal (∼10 µm in thickness and ∼70 µm in the longest dimension), which was flash-frozen in liquid nitro-gen, was milled away with a gallium FIB under cryogenic conditions, and a part of the crystal itself was thinned into a ∼210 nm-thick lamella with the ion beam. The frozen sample was then transferred into an electron cryo-microscope, and a nanovolume of ∼1400 × 1400 × 210 nm of the BR lamella was exposed to 200 kV electrons at a fluence of ∼0.06 e Å-2. The resulting electron diffraction peaks were detected beyond 2.7 Å resolution (with an average peak height to background ratio of >2) by a CMOS-based Ceta 16M camera. The results demonstrate that cryo-FIB milling produces high-quality lamellae from crystals grown in lipidic mesophases and pave the way for 3D electron crystallography on crystals grown or embedded in highly viscous media.
Keywords: focused ion beam milling; lamella preparation; electron diffraction; membrane protein crystals grown in meso; lipidic cubic phases